Water Flow Velocity Analysis on Small-Scale Spillway Using Particle Image Velocimetry (PIV) - Nurhikmah F.; Zawawi M.H.; Hassan N.H.; Zahari N.M. (Springer Science and Business Media Deutschland GmbH, 2025)
The spillway design for a dam project needs to deal with many hydraulics issues based on the study of the physical model. This study aims to investigate the flow characteristic and the effect of velocity along the spillway structure. The durability of the spillway structure was identifying by the area that experienced high velocity. In this study, twelve measurements points with three different velocity flow (0.025, 0.045 and 0.060m/s) along the spillway were conducted. The scale-down physical model for the spillway was conducted for particle image velocimetry (PIV) analysis. Result from the study shows that the highest velocity value is at point Q3 on Case 3 which is 0.040m/s and the lowest is at points P5 and S5 on Case 1 with 0.005m/s. It can be concluded that the velocity flow is higher near the energy dissipater parts compared to the stilling basin area due to the water force acting on the spillway structure. To ensure the structural integrity sustainability, further study on the future mitigation measures can be taken. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.